A nanoporous Cu-Ag thin film at the Cu-Ag-Zn alloy surface by spontaneous dissolution of Zn and Cu in different degrees as a highly sensitive non-enzymatic glucose sensor. (10th October 2019) - Liu, Sanmei; Liu, Bingwu; Gong, Chenfan; Li, Zelin
Abstract: In this article, we present a new dealloying way to fabricate a stable nanoporous Cu-Ag bimetallic thin film as a glucose sensor. The nanoporous Cu-Ag thin film is obtained under a mild condition simply by immersing a Cu-Ag-Zn alloy disk electrode (with minor Ag) of 2-mm diameter in 1 M KOH solution at room temperature for a short time of 3 h. The metallic Zn and Cu at the ternary alloy surface are automatically dissolved completely and partially via oxidation reactions with the solvent H2 O and the dissolved O2, respectively, leaving a nanoporous structure on the disk substrate. The method is very facile, green and cost-effective. The prepared nanoporous Cu-Ag thin film consists of small nanoparticles. The presence of lesser Ag prevents the small Cu-Ag nanoparticles from agglomeration and enhances the electro-oxidation of glucose compared with the dealloyed Cu-Zn electrode. The prepared nanoporous Cu-Ag film can serve as an advanced glucose sensor with a high sensitivity of 3572 μA mM −1  cm −2, a low detection limit of 0.37 μM, a wide linear range up to 6 mM, excellent reproducibility (RSD < 5%), short response time (4 s), and long-term stability of 4 weeks. The glucose sensor has been satisfactorily applied to the determination of glucose concentration in human serum. This automatic dealloying method is expected to fabricate other stable nanoporous bimetallic films for non-enzymatic glucose sensing and other applications. Graphical abstract: Image 1 Highlights: A nanoporous Cu-Ag film is fabricated by auto-dealloying in 1 M KOH solution. Ιt involves complete dissolution of Zn and partial dissolution of Cu at the surface. Minor Ag stabilizes the Cu-Ag nanoparticles and enhances electro-oxidation of glucose. The method is facile, green, low-cost, and applicable to make more bimetal sensors. The nanoporous Cu-Ag film can serve as an advanced glucose sensor.